Sulfur amino acid requirements for pullets in growth and pre-laying trials - Silva, E. P. [UNESP]; Sakomura, N. K. [UNESP]; Dorigam, J. C.P. [UNESP]; Lima, M. B. [UNESP]; Malheiros, E. B. [UNESP]; Fernandes, J. B.K. [UNESP] (CSIRO Publishing, 2021)
Context: To obtain a good performance of the hens in the laying phase, adequate nutrition in the growth and pre-laying phase is necessary, especially for meeting amino acid requirements that are related to development of reproductive organs (ovary and oviduct). Aims: The objective of the present study was to predict the requirements for methionine (Met) plus cystine (Cys) from the growth of the body, feathers and reproductive organs of laying hens. Methods: The model estimates Met+Cys requirements as the relationship between the deposition of Met+Cys into three compartments (body, feathers, and reproductive organs) and their utilisation efficiency. The efficiency of utilisation was determined by a linear regression between Met+Cys deposition and intake for pullets aged 14-28, 56-70 and 98-112 days. Protein weight and deposition in the body and feathers were determined by the comparative slaughter method. The Gompertz function was used to model body, feathers, ovary, oviduct and liver weight against age. Key results: Our results showed that the inclusion of parameters descriptive of the growth of reproductive organs and the correction for feather losses in the model enabled Met+Cys requirements for growth in pre-laying trials to be predicted with a greater precision. Conclusions: The model developed in this study for determining the Met+Cys requirements for Dekalb White pullets could be extended, provided the necessary adjustments are made, to other amino acids, strains and species. Implications: Meeting Met+Cys requirements in the phase of maximum growth of the reproductive organs (weeks) contributes to the uniformity of the age when the pullets reach sexual maturity and, consequently, start the egg production.
Keywords: efficiency of utilisation; feather loss; methionine; ovary; oviduct